2021
DOI: 10.3389/fpsyg.2021.678752
|View full text |Cite
|
Sign up to set email alerts
|

Germaphobia! Does Our Relationship With and Knowledge of Biodiversity Affect Our Attitudes Toward Microbes?

Abstract: Germaphobia – a pathological aversion to microorganisms – could be contributing to an explosion in human immune-related disorders via mass sterilization of surfaces and reduced exposure to biodiversity. Loss of biodiversity and people’s weaker connection to nature, along with poor microbial literacy may be augmenting the negative consequences of germaphobia on ecosystem health. In this study, we created an online questionnaire to acquire data on attitudes toward, and knowledge of microbes. We collected data on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…They found a direct positive relationship between a positive attitude and knowledge of microbes and the frequency and duration of visits to natural environments. They also found that a viral-centric focus of microbes and lack of knowledge about microbial diversity, such as occurred with the Covid-19 scare, was more likely to be associated with an overall negative view of microbes and increased germaphobia [113].…”
Section: Human Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a direct positive relationship between a positive attitude and knowledge of microbes and the frequency and duration of visits to natural environments. They also found that a viral-centric focus of microbes and lack of knowledge about microbial diversity, such as occurred with the Covid-19 scare, was more likely to be associated with an overall negative view of microbes and increased germaphobia [113].…”
Section: Human Gutmentioning
confidence: 99%
“…Governmental decrees designed to isolate healthy humans from each other and from nature only contribute to microbiome and physiological degradation [5,56]. Additionally, Robinson et al [113] posited that germaphobia has contributed to the prevalence of immune-driven disorders and mental health conditions and that our weaker connection to nature has further fostered immune related chronic disease. These researchers surveyed 1,184 individuals (the majority in the UK)…”
Section: Human Gutmentioning
confidence: 99%
“…A greater understanding of psychological relationships with nature, biodiversity, and potentially beneficial microbes, and how those attitudes and values intersect with biophysiological markers, will also be necessary. To this end, some have called for a deeper understanding of “microbial literacy” and how it might act as a pathway to more positive and constructive attitudes toward the microorganisms that underpin the ecosystems that sustain health along the personal, community, and planetary health continuum 113 …”
Section: Nature‐based Solutions: Tangible Actions With Co‐benefits Fo...mentioning
confidence: 99%
“…To this end, some have called for a deeper understanding of “microbial literacy” and how it might act as a pathway to more positive and constructive attitudes toward the microorganisms that underpin the ecosystems that sustain health along the personal, community, and planetary health continuum. 113 …”
Section: Nature‐based Solutions: Tangible Actions With Co‐benefits Fo...mentioning
confidence: 99%
“…This unbalanced view of microbes is exacerbated by the overhyped media coverage during outbreaks of infected food (Neutro 2016 , Ivanhoe 2019 ). Society lacks a balanced view of the many positive roles bacteria have on our health, resulting in public fear of the words “bacteria”, “microbes”, and “germs” and can manifest into germaphobia (Robinson et al 2021 ). The resulting “gap” can lead to an artificial separation between the fields of Arts and Sciences, and in the public’s understanding and knowledge of the important positive role of microbes.…”
Section: Introductionmentioning
confidence: 99%